A resilient ice cover over the southernmost Mendeleev Ridge during the late Quaternary - Song, T.; Hillaire-Marcel, C.; de Vernal, A.; Liu, Y. (Boreas, 2024)

Challenging Radiocarbon Chronostratigraphies in Central Arctic Ocean Sediment - Hillaire‐Marcel, C.; De Vernal, A.; Rong, Y.; Roberge, P.; Song, T. (Geophysical Research Letters, 2022)
Abstract Based on the analysis of fish otolith assemblages from surface sediments of the Lomonosov Ridge (Arctic Ocean), we demonstrate that the very low Holocene sedimentation rates and winnowing of fine sediments result in the mixing of the whole Holocene populations at the sediment surface. Specimens from the Marine Isotope Stage (MIS) 3 or older could even be recovered in the surface due to a sedimentary hiatus at some locations in the central Arctic during the last glacial maximum. Two examples illustrate that 14 C‐stratigraphies from planktic foraminifers in underlying cored sediments reflect the mixing between Holocene and MIS 3 or older populations, thus invalidating continuous age‐depth inferences based on 14 C ages. Hence, much caution is required when attempting to set paleoceanographic reconstructions based on 14 C chronologies in a low sediment accumulation rate environment such as the central Arctic Ocean. Already published paleoceanographic reconstructions from this area might thus require some revisions. , Plain Language Summary Radiocarbon ages of microfossils (fish otoliths) collected at the surface sediments of the Lomonosov Ridge, in the central Arctic Ocean, indicate that all populations that developed during the present interglacial are mixed within the approximately 1 cm‐thick surface layer. Fossil assemblages occasionally include specimens from older warm intervals. The stacking of fossil spanning thousands of years is due to the very low sediment accumulation rate of the area, the post‐depositional winnowing of fine sediments and mixing by benthic organisms. These process result in the impossibility to document the faunal evolution in the central Arctic Ocean during the last few tens of thousands of years using such fossils. , Key Points Fish otolith radiocarbon age distributions in surface sediments illustrate the mixing of Holocene and pre‐Last Glacial Maximum populations Low sedimentation rates, particle winnowing and sedimentary gaps may impact microfossil mixing and 14 C chronologies Published paleoclimate/paleoceanographic records from similar sites might thus require some reinterpretation

Opposed east-west climate response of the Arctic Ocean during the present interglacial - de Vernal, A.; Hillaire-Marcel, C.; Song, T.; Radi, T.; Falardeau, J.; Liu, Y. (Science Advances, 2024)

A New Chronology of Late Quaternary Sequences From the Central Arctic Ocean Based on “Extinction Ages” of Their Excesses in^231 Pa and^230 Th - Hillaire‐Marcel, C.; Ghaleb, B.; De Vernal, A.; Maccali, J.; Cuny, K.; Jacobel, A.; Le Duc, C.; McManus, J. (Geochemistry, Geophysics, Geosystems, 2017)
Abstract Merging the late Quaternary Arctic paleoceanography into the Earth's global climate history remains challenging due to the lack of robust marine chronostratigraphies. Over ridges notably, low and variable sedimentation rates, scarce biogenic remains ensuing from low productivity and/or poor preservation, and oxygen isotope and paleomagnetic records differing from global stacks represent major impediments. However, as illustrate here based on consistent records from Mendeleev‐Alpha and Lomonosov Ridges, disequilibria between U‐series isotopes can provide benchmark ages. In such settings, fluxes of the particle‐reactive U‐daughter isotopes 230 Th and 231 Pa from the water column, are not unequivocally linked to sedimentation rates, but rather to sea‐ice rafting and brine production histories, thus to the development of sea‐ice factories over shelves during intervals of high relative sea level. The excesses in 230 Th and 231 Pa over fractions supported by their parent U‐isotopes, collapse down sedimentary sequences, due to radioactive decay, and provide radiometric benchmark ages of approximately 300 and 140 ka, respectively. These “extinction ages” point to mean sedimentation rates of ∼4.3 and ∼1.7 mm/ka, respectively, over the Lomonosov and Mendeleev Ridges, which are significantly lower than assumed in most recent studies, thus highlighting the need for revisiting current interpretations of Arctic lithostratigraphies in relation to the global‐scale late Quaternary climatostratigraphy. , Plain Language Summary The Arctic Ocean represents a major component of the Earth climate system notably with regard to the Arctic amplification and freshwater fluxes toward the global ocean. Understanding its role versus the global climate history of the recent glacial/interglacial cycles remains challenging due to the lack of robust chronology of marine sedimentary archives. In the present study, we demonstrate that the decay of Uranium series isotopes in sediments from major Arctic ridges provide benchmark ages for the last ∼300,000 years and support the concept of a “sediment‐starved” environment in the central Arctic Ocean. , Key Points New chronology of late Quaternary marine sequences from the central Arctic Mean sedimentation rates of the order of millimeters per thousand years over ridges Highly discontinuous ice‐rafted sedimentation over ridges with gaps